Effects of pH, myoglobin form, and endpoint temperature on cooked ground beef color - Schoenbeck, M.K.; Kropf, Donald H.; Hunt, Melvin C.; Hawthorne, S.; Stroda, Sally L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Beef quadriceps muscles from nine pH groups (5.5 - 6.4 in .1 increments) were ground; mixed with fat (20%); formed into patties whose myoglobin was in either the oxy or deoxy state; and cooked to four endpoint temperatures (150, 160, 170, or 180°F). Internal cooked patty color was evaluated visually and instrumentally. Patties containing deoxymyoglobin with pH 6.2 or higher and cooked to 150 and 160°F were redder visually and instrumentally than those with a lower pH. Similar trends, but not as pronounced, were observed with patties containing oxymyoglobin. Deoxymyoglobin was more resistant to denaturation and, thus, made patties more susceptible to persistent red color and at a lower pH than those with oxymyoglobin.
Keywords: Beef; Ground Beef; Cooked color; pH; Myoglobin form